Conceptual Understanding of Class V Students Judging from Curiosity on Learning Models Group Investigation with Hands on Activity Assisted by Teaching Aids. - Rini, Zulmi Roestika; Kartono, Kartono; Hidayah, Isti (Universitas Negeri Semarang, 2019)
The purpose of this study (1) to test the effectiveness of the Group Investigation learning model with Hands on Activity assisted by teaching aids on conceptual understanding (2) to describe the understanding of the concept of class V students in terms of students' curiosity. The method used is the research Mix Method, and the design Concurrent Embedded. This research was conducted at the Semarang Elementary School Lab. The population of this study was the fifth grade students of the SD Lab School Semarang in the academic year 2017/2018. From the V classes at the Semarang Elementary School Lab 2 classes were randomly selected to get the VA class as the experimental class subjected to the learning model Group Investigation with Hands on Activity assisted by teaching aids and the VB class as the control class subjected to the expository learning model. Learning Group Investigation assisted by Hands On Activity with teaching aids on volume material and beam surface area in class V students proved effective. Students with high categories with high curiosity have been able to reach all four aspects of the ability to understand mathematical concepts; students with curiosity are able to achieve three aspects. the ability to understand mathematical concepts, and for students with low curiosity can only achieve one aspect of the ability to understand mathematical concepts.